Investigating Inclusiveness and Backward Compatibility of IEEE 802.11be Multi-link Operation - Medda, Daniele (2022)
Nowadays is not possible to avoid considering the coexistence and the fusion of different wireless technologies as completely separated entities. The ever-growing number of devices employing multi-RATs (Radio Access Technologies) that require continuous wireless connectivity is posing great challenges. Furthermore, the requirements in terms of both throughput and latency originated by the use cases, are pushing the current technologies to their limits, especially for indoor dense deployments that are usually covered by Wi-Fi. The IEEE 802.11 Working Group is currently tackling such challenges by working on a new amendment of the standard (namely 802.11be), which introduces, among other novelties, the multi-link operation (MLO). Through MLO, the target is to achieve simultaneous transmission over multiple bands to obtain massive bitrate up to 40 Gbps. The introduction of MLO poses challenges on the coexistence with older legacy devices in mixed networks. This contribution explores how the coexistence of legacy IEEE 802.11 devices and new IEEE 802.11be devices realizing the proposed multi-link feature can be improved by using an appropriate static band assignment policy. Another issue is how the overall network behaves when varying the number of devices and the legacy/new nodes ratio. Simulations for three different band allocation cases close to reality are developed. Performance results in terms of aggregated, average throughput and fairness are derived for different conditions.